Cost savings with a new screening algorithm for pulmonary arterial hypertension in systemic sclerosis. Issue 11 (November 2015) - Quinlivan, A.; Thakkar, V.; Stevens, W.; Morrisroe, K.; Prior, D.; Rabusa, C.; Youssef, P.; Gabbay, E.; Roddy, J.; Walker, J. G.; Zochling, J.; Sahhar, J.; et al.
Abstract: Background: Screening for pulmonary arterial hypertension (PAH) in systemic sclerosis (SSc) is now standard care in this disease. The existing Australian Scleroderma Interest Group algorithm (ASIGSTANDARD ) is based on transthoracic echocardiography (TTE) and pulmonary function tests (PFT). Recently, ASIG has derived and validated a new screening algorithm (ASIGPROPOSED ) that incorporates N‐terminal pro‐B‐type natriuretic peptide level together with PFT in order to decrease reliance on TTE, which has some limitations. Right heart catheterisation (RHC) remains the gold standard for the diagnosis of PAH in patients who screen 'positive'. Aim: To compare the cost of PAH screening in SSc with ASIGSTANDARD and ASIGPROPOSED algorithms. Methods: We applied both ASIGSTANDARD and ASIGPROPOSED algorithms to 643 screen‐naïve SSc patients from the Australian Scleroderma Cohort Study (ASCS), assuming a PAH prevalence of 10%. We compared the costs of screening, the number of TTE required and both the total number of RHC required and the number of RHC needed to diagnose one case of PAH, and costs, according to each algorithm. We then extrapolated the costs to the estimated total Australian SSc population. Results: In screen‐naïve patients from the ASCS, ASIGPROPOSED resulted in 64% fewer TTE and 10% fewer RHC compared with ASIGSTANDARD, with $1936 (15%) saved for each case of PAH diagnosed. When the costs were extrapolated to the entire Australian SSc population, there was an estimated screening cost saving of $946 000 per annum with ASIGPROPOSED, with a cost saving of $851 400 in each subsequent year of screening. Conclusions: ASIGPROPOSED substantially reduces the number of TTE and RHC required and results in substantial cost savings in SSc‐PAH screening compared with ASIGSTANDARD .